Effects of rice blast biocontrol strain Pseudomonas alcaliphila Ej2 on the endophytic microbiome and proteome of rice under salt stress - Zeng, Qingchao; Man, Xiaowu; Huang, Zeyang; Zhuang, Lubo; Yang, Hanmeng; Sha, Yuexia (Frontiers in Microbiology, 2023)
Soil salinity is a prevalent environmental stress in agricultural production. Microbial inoculants could effectively help plants to alleviate salt stress. However, there is little knowledge of the biocontrol strain P. alcaliphila Ej2 mechanisms aiding rice plants to reduce the adverse effects caused by salt stress. We performed integrated field and greenhouse experiments, microbial community profiling, and rice proteomic analysis to systematically investigate the Ej2 mechanism of action. The results displayed that biocontrol strain Ej2 increased shoot/root length and fresh/dry weight compared with control under salt stress. Meanwhile, strain Ej2 has the ability to control rice blast disease and promote rice growth. Furthermore, the microbial community analysis revealed that the alpha diversity of Ej2-inoculated plants was higher than the control plants, expect the Shannon index of the bacterial microbiome and the Ej2 inoculated samples clustered and separated from the control samples based on beta diversity analysis. Importantly, the enriched and specific OTUs after Ej2 inoculation at the genus level were Streptomyces, Pseudomonas, Flavobacterium, and Bacillus. Moreover, we observed that Ej2 inoculation influenced the rice proteomic profile, including metabolism, plant-pathogen interactions, and biosynthesis of unsaturated fatty acids. These results provide comprehensive evidence that Ej2 inoculation induced the rice endophytic microbiome and proteomic profiles to promote plant growth under salt stress. Understanding the biocontrol strain effects on the endophytic microbiome and rice proteomics will help us better understand the complex interactions between plants and microorganisms under salt stress. Furthermore, unraveling the mechanisms underlying salt tolerance will help us more efficiently ameliorate saline soils.